1994
DOI: 10.21273/hortsci.29.4.256
|View full text |Cite
|
Sign up to set email alerts
|

Staminate and Pistillate Flower Production of Summer Squash in Response to Planting Date

Abstract: Additional index words. flower sex, sex ratio, Cucurbita pepo Abstract. Staminate and pistillate flower production in summer squash (Cucurbita pepo L.) fluctuates readily in response to the various crop production environments throughout the southeastern United States. 'Dixie', 'Senator ', 'Lemondrop', 'Meigs', and 'Elite' squash were planted at various times over 2 years in Griffin, Ga., to determine the effect of planting date on staminate and pistillate flower counts for the first 2 weeks of flowering. Stam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…In eight cucurbit species, including C. pepo, Whitaker (1931) reported staminate flowers outnumbered pistillate flowers at all times and often reached anthesis 1 week prior to the first pistillate blossom. NeSmith et al (1994) found that floral sex ratios varied among summer squash [C. pepo var. melopepo (L.) Alef.]…”
Section: Resultsmentioning
confidence: 99%
“…In eight cucurbit species, including C. pepo, Whitaker (1931) reported staminate flowers outnumbered pistillate flowers at all times and often reached anthesis 1 week prior to the first pistillate blossom. NeSmith et al (1994) found that floral sex ratios varied among summer squash [C. pepo var. melopepo (L.) Alef.]…”
Section: Resultsmentioning
confidence: 99%
“…With the recent concern about the pollination crisis in crop plants 24,25 , the highly skewed flower sex expression may further affect crop production in monoecious plant species. We have assessed the flower sex expression during the peak flowering (pistillate flowering and fruiting) period of the respective crop species, which is likely to vary with different phases of flowering, seasons and plant maturity 26,27 . Studies that have investigated variables affecting yield in cucurbit plants have rarely incorporated flower sex expression in their models 4,6,9,11 .…”
mentioning
confidence: 99%
“…The higher temperature during growth period in 2011 enhanced the early production of pistillate flowers leading to early harvesting. Nesmith & Hoogenboom (1994) also stated that production of pistillate flowers in summer squash was accelerated by high temperature. Availability period of vegetable marrow was also influenced significantly by seedlings age.…”
Section: Resultsmentioning
confidence: 99%